A Barrel of Oil or a Bottle of Wine: How Do Global Growth Dynamics Affect Commodity Prices?*. (27th March 2014) - Cevik, Serhan; Saadi Sedik, Tahsin
Abstract This paper explores empirically the causes of extreme fluctuations in commodity prices from January 1990 to June 2010 and seeks to identify the relative contribution of advanced and emerging market economies to the changes in commodity prices. Our assumption is that analyzing two very distinct goods—crude oil and fine wine—helps to identify common determinants of commodity prices. We find that the growth rate of global aggregate demand is the key macroeconomic determinant of the fluctuations in both crude oil and fine wine prices over the sample period. While advanced economies account for more than half of global consumption, emerging market and developing economies make up the bulk of the incremental change in demand, thereby having a greater weight in commodity price formation. The coefficient of emerging market industrial output growth is about three times as high as that of advanced economies in oil price regressions and almost five times as powerful in fine wine price regressions. The results also show that the shift in the composition of aggregate commodity demand is a recent phenomenon. (JEL Classifications: Q11, Q39, Q41, Q43)